From sensors to sensations: considerations about esthesiologic body and the use of wearables technologies in artistic performances (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
Our objective in this article is to analyze the use of wearable technologies in the scope of artistic performance. Our premise is that the artist's body connected by devices and expanded in the cyberspace is enclosed in a distinct digital form of communication that reconfigures the notion of bodily presence. Therefore, it engenders other ways of understanding the relationship of the performer's body with other bodies and with things, enhancing the expressive possibilities of affecting and being affected. The considerations presented are based on the philosophical notions of Merleau-Ponty, especially the concepts of the estheseologic body and intercorporeality.
Keywords: Performance mediated by devices; Wearable technologies; Esthesiologic body; Intercorporeality